Answer:
The correct answer is C. (6,0).
Explanation:
1. Arrange both equations to be equal to y which is y=6-x/-4 and y=12-2x/2
2. Set the equal to each other: 6-x/-4=12-2x/2 and solve for x6-x/-4=12-2x/2 cross multiply to get 2(6-x)=-4(12-2x) and distribute to get 12-2x=-48+8x Subtract 12 from both sides:-2x=-60+8x subtract 8x from both sides: -10x=-60 divide by 10 on both sides: x=6
3. Plug the x value of 6 into one of the original equations (we'll do x-4y=6) to get (6)-4y=6
4. Solve for y subtract 6 from both sides: -4y=0 Divide by -4 on both sides: y=05. The y coordinate is 0, and the x coordinate is 6, so (6,0).
For the solution, the x coordinate always comes first, then the y coordinate.